MAPPING OF LANGUAGE BRAIN AREAS IN PATIENTS WITH BRAIN TUMOUR USING MEG - ALI HYDER, RASHA (2015)
Language cortex in the human brain shows high variability among normal individuals. Particularly, in the presence ofbrain tumors, language specific areas may also be shifted from their original positions because of the growth of the tumor. Mapping the precise location of language areas is important before surgery to avoid causingpostoperative languagedeficitsespeciallywhen the surgery is performed in the left hemisphere whichhas greaterrepresentation oflanguage functions in most ofright handed people. The main goal of this study is to identify brain areas associated with silent reading among different Malay patients with left brain tumors using magnetoencephalography (MEG). Given the complexity of language function and the expected variability associated with the presence of brain tumors, we undertook this study. Six brain tumor patients underwentMEG recording and MRI scanning.